Cyber Bullying Prevention And Handling Through Hindu Family Education - Sudarsana, I Ketut; Lali Yogantara, I Wayan; Ekawati, Ni Wayan (LPM IHDN Denpasar, 2019)
Technological developments have positive and negative impact on teenagers in particular. The most common negative impact of technology is cyber bullying. In globalization era and technological development, nowadays computer can produce multifunctional internet. All good and evil behavior can be done on social media. Before the development of the internet, cyber bullying actor committed their crimes in the real world. Cyber bullying actor can hurt and make many individuals uncomfortable in their lives. The crime is called bullying. Nowadays, the bullying can be done through any other media indirectly such as social media and it called cyber bullying. According to the Hinduja and Patching Cyber-Bullying researcher, the behavior is described as intentional action by sending electronic text (e-mail), or recording images that are usually uploaded to social media (youtube). The contents uploaded such as mocking, harassing, threatening, harassing, or insulting.